Revisiting the structure of copolymer via anionic hybrid copolymerization of methyl methacrylate and ε-caprolactone. (8th November 2022) - Yang, Hongjun; Yao, Hongxin; Feng, Kaifeng; Zhang, Guangzhao
Abstract: Anionic hybrid copolymerization of vinyl and cyclic monomers provides a powerful strategy to synthesize heteropolymers. Yet, there are some open questions regarding its mechanism and the structure of the resulted polymer. We reported that the copolymer (Poly(MMA- co -CL)) of methyl methacrylate (MMA) and ε-caprolactone (CL) via such copolymerization was random. However, a recent study proposed that the copolymer might be simple graft one with poly(methyl methacrylate) (PMMA) as the main chain and poly(ε-caprolactone) (PCL) as the graft chain. In this study, we synthesized a model graft copolymer (PMMA- g -PCL) by using a combination of reversible complexation-mediated polymerization and ring-opening polymerization, and made comparison with Poly(MMA- co -CL) in their properties and hydrolysis. Differential scanning calorimeter (DSC) measurements show that the graft copolymer PMMA- g -PCL possesses two glass transitions and a melt peak. In contrast, Poly(MMA- co -CL) exhibits only one glass transition without a melt peak because it is amorphous, clearly indicating that it is random. Proton nuclear magnetic resonance ( 1 H NMR) measurements reveal that the hydrolysis of PMMA- g -PCL yields only PMMA oligomers. However, the hydrolyzed products of Poly(MMA- co -CL) consist of MMA and CL units. The facts further indicate that the copolymer Poly(MMA- co -CL) is random. Considering that the transesterification reactions are unavoidable in the anionic hybrid copolymerization, the copolymer should consist of random main chain and random branches. Graphical abstract: Image 1 Highlights: The present study demonstrates that anionic hybrid copolymerization of MMA and CL generally yields random copolymer but not graft copolymer. Transesterification is not the essential step in the anionic hybrid copolymerization, but it can cause branching of the copolymer. The hybrid copolymer of MMA and CL consists random main chain and random branches.